Antibacterial properties of natural tropical fruit vinegars against Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus bacteria. Issue 1 (December 2020) - Mokhtar, Seri Intan; Pahirulzaman Xuan, KAK Fong Yung
Abstract: Various researchers have found that vinegar has antibacterial effect on different types of pathogenic bacteria which make it useful for a varieties of application in medical, food preservation and as cosmetic ingredient. Many new emerging tropical fruits vinegars were not tested for antibacterial properties especially for skin and acne causing treatment. Therefore, this study aim is to test several tropical fruits vinegar in order to determine their ability against skin and acne causing bacteria ultimately could lead to application of effective vinegars in personal care and cosmetic products. Tropical fruit vinegars such as pineapple, mango, coconut, dokong and rambutan vinegars were tested for the presence of acetic acid, titratable acid, pH and anti-microbial properties against acne causing bacteria Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus . The presence of acetic acid content in the vinegar samples was determined using HPLC analysis against 100% glacial acetic acid standard and shown to be between 6.444, 6.959, 5.832, 6.484 and 6.373 min. Titratable acidity range lied between 1.14 ± 0.06% to 3.26 ± 0.09% of which rambutan vinegar showing highest acetic acid content while pineapple vinegar giving the lowest value. The pH value among five vinegar samples fell within the range of 3.06 to 3.65 of which pineapple vinegar has the lowest value and coconut vinegar had the highest pH. Antimicrobial properties of different tropical fruit vinegar samples with different percentage of acetic acid content in samples comprised of 0.5%, 1.0%, 1.5%, 2.0%, 2.5% and 3.0% were determined by antimicrobial disk diffusion assay on Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus . Clear zone of inhibition could be observed at 1% acetic acid in all samples, ranging from 7.8 mm to 8.6 mm against main acne causative bacteria, Propionibacterium acnes indicating that the vinegars has antibacterial properties against the bacterium